Pendampingan Mitigasi Risiko Perhitungan PPh Pasal 21 bagi Suami Istri yang Memiliki Nomor Pokok Wajib Pajak (NPWP) Berbeda dalam Rangka Menyambut Implementasi Coretax: Risk Mitigation Assistance in Calculating Tax Article 21 for Husbands and Wives with Different Taxpayer Identification Numbers in Preparation for the Implementation of Coretax - Cheisviyanny, Charoline; Sari, Vita Fitria; Permata, Shintya Dwi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Changes in tax policy through Law Number 7 of 2021 concerning the Harmonization of Tax Regulations and the implementation of the National Identification Number (NIK)-based tax administration system (Coretax) have created a need to improve tax literacy for married couples with different Taxpayer Identification Numbers (NPWP). This community service activity aims to provide risk mitigation assistance and improve participants’ understanding of SPT reporting obligations and the use of the Coretax system. The implementation method uses an educational and participatory approach through stages of regulatory socialization, simulation training on calculating Income Tax Article 21 for combined and separate NPWP scenarios, and technical assistance on using the Coretax Administration System (CTAS). Evaluation was conducted using pre- and post-knowledge questionnaires, practical observations, and satisfaction questionnaires. The results showed that before the activity, the majority of participants (81.82%) did not understand the procedures for tax reporting based on the Coretax Administration System (CTAS). However, after participating in the simulation-based and hands-on assistance program, more than 70% of participants showed significant improvements in their tax calculation and reporting skills in accordance with regulations. This program demonstrated that an educational approach based on outreach, simulations, and technical training effectively improved tax literacy among married couples and their readiness for Coretax implementation. Replication of the program with a larger number of participants and broader collaboration with the Directorate General of Taxes is recommended.